Indicadores clínicos preliminares para a constituição do sujeito falante - Evangelista, Fábia Regina (2011)
INTRODUCTION: In the area of Speech-Language Pathology, studies that link clinical indicators and the constitution of the speaking subject are incipient, although researches about this theme could contribute to health promotion actions. To propose clinical indicators in the Speech-Language Pathology clinic, one must consider the peculiarities of this practice in its articulation among subjective aspects, noting that language symptoms are related to the effects of the relationship of the subject with the other/Other, the body, the language and the speech. OBJECTIVE: To propose preliminary clinical indicators for the constitution of the speaking subject. METHOD: The preliminary clinical indicators for the constitution of the speaking subject were based on pillars drawn up by Kupfer et al. (2003) for the constitution of the subject, by the model of the language symptoms approached by GOUVÊA (2007), and by the LEMOS (2002) proposal for language acquisition as a change in the position of the infans in relation to the other, language and speech. Analysis of Speech-Language academic reports from users who had been attended by the Speech-Language Pathology sector in the period from 2006 to 2009 in three Basic Health Units located in the Eastern Zone of São Paulo. Inclusion criteria: children between 2 and 6 years old, with speech evaluation and diagnosis of articulation disorders, stuttering or delayed speech. Exclusion criteria: children presenting speech and language disorders secondary to diseases of organic origin. Procedures: The data extracted from Speech-Language academic reports were organized in 2007 Excel spreadsheets in order to select the subjects of the research and avoiding duplicity. The analysis focused on parent s complaints and on their sayings reported in the interviews. Criteria for interpretation of data: Data interpretation focused on the parent s sayings about their child with speech and language symptoms, grouped by similarity, based on four pillars that support the constitution of the speaking subject: supposing/denying a speaking subject, recognition/denial of the speaking subject, recognition/denial of the significant and the responsiveness of the subject to the speech of the other. RESULTS AND CONCLUSIONS: The initial sample comprised 422 Speech-Language academic reports. From this sample, it was selected the ones related to the subjects whose characteristics matched the selection criteria, reaching 88 reports/subjects. From the parent s sayings about their complaints and those extracted from the interviews, 12 preliminary clinical indicators for the constitution of the speaking subject were established. These indicators point to a possibility of occurrence of speech and language disorders, allowing effective intervention in promoting the health of the speaker. The results suggest the importance of the actions of the speech therapist on basic health services before the symptoms emerge in speech and language